2016
DOI: 10.1177/1715163516640812
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 polyunsaturated fatty acid supplementation in the prevention of cardiovascular disease

Abstract: It is estimated that over 70% of Canadians take 1 or more natural health products, such as omega-3 polyunsaturated fatty acids (PUFAs) for cardiovascular protection. We sought to systematically identify and assess the best currently available evidence investigating the use of omega-3 PUFAs for the prevention of cardiovascular disease. clinical review 640812C PHXXX10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
0
23
0
2
Order By: Relevance
“…Due to the large number of determinants affecting vascular status and inflammation, all studies discussed in this section are rather heterogeneous with respect to outcomes considered and parameters measured, thereby the data are difficult to compare and summarize. The incorporation of n-3 PUFAs in cell membranes modifies eicosanoid production [ 13 ]. Phang et al [ 57 ], measuring platelet aggregation capacity (as platelet lag time after collagen addition) on 94 men and women, observed that both EPA and DHA were effective in reducing aggregation (−11.8% EPA, −14.8% DHA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the large number of determinants affecting vascular status and inflammation, all studies discussed in this section are rather heterogeneous with respect to outcomes considered and parameters measured, thereby the data are difficult to compare and summarize. The incorporation of n-3 PUFAs in cell membranes modifies eicosanoid production [ 13 ]. Phang et al [ 57 ], measuring platelet aggregation capacity (as platelet lag time after collagen addition) on 94 men and women, observed that both EPA and DHA were effective in reducing aggregation (−11.8% EPA, −14.8% DHA).…”
Section: Resultsmentioning
confidence: 99%
“…Similar investigations conducted on an indigenous population traditionally consuming large quantities of sea foods [ 9 ] in Canada evidenced the beneficial effects of n-3 PUFAs-rich foods for cardiovascular risk and CVD-related mortality reduction. Nevertheless, recent reviews examining subjects at high risk for CVD, reported discordant findings between no effects vs. beneficial effects of n-3 PUFAs supplementation for the prevention of CVD [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in another recent systematic review of placebo-controlled randomised controlled trials (RCTs) of ω-3 PUFAs supplementation (that enrolled over 1000 patients with follow-up greater than one year) and meta-analysis of RCTs, carried out by Walz, Barry and Koshman [ 55 ], it was found that there is currently a lack of evidence to support the routine use of ω-3 PUFAs in the primary and secondary prevention of CVDs. It was also proposed by the authors of this study that pharmacists are ideally situated to engage patients in the discussion of the lack of benefit and possible risk of ω-3 PUFA supplements (since ω-3 PUFAs can increase the risk of bleeding and may interact with other medications that affect haemostasis, such as antiplatelet agents and warfarin) [ 55 ].…”
Section: Marine Originmentioning
confidence: 99%
“…However, despite the overwhelming amount of evidence on the beneficial effects of ω-3 PUFAs on human health, some controversy remains since several systematic reviews and meta-analyses have illustrated that there is insufficient evidence for this notion, with many studies highlighting the lack of benefit and possible risks associated with the consumption of ω-3 PUFA supplements. Furthermore, some of these studies indicate that the beneficial effects of fish intake on cerebrovascular risk are likely to be mediated through the interplay of a wide range of nutrients abundant in fish [ 52 , 53 , 54 , 55 , 56 ]. However, within the last decade there is evidence that when ω-3 PUFAs (such as EPA and DHA) are combined to PLs, they are more efficiently incorporated into tissue membranes and at much lower doses than when these PUFAs are combined to TAGs.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of crude proteins and amino acid composition differences between them were caused by enriched silk fibers in enlarged silk glands in mature silkworm larvae . All tested silkworm larval powders contained high amounts of Ω-3 (n-3) unsaturated fatty acids, which are one of the most popular health improvement supplements (Walz et al, 2016). National Institute of Agricultural Science (NIAS) is securing total 340 silkworm pure breeds that have various phenotypes such as colors and sizes of cocoons, female's fecundity, etc.…”
Section: Introductionmentioning
confidence: 99%